Pengaruh profitabilitas, pertumbuhan asset dan ukuran perusahaan terhadap struktur modal pada perusahaan manufaktur di Bursa Efek Indonesia (BEI) - Fatmah Watty Pelupessy (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
The purpose of scientific writing is to know the effect of Profitability, Asset Growth and Firm Size Of Capital Structure On Manufacturing Company in Indonesia Stock Exchange (BEI) Period 2010-2014. The analysis technique used is a statistical test with multiple regression analysis and hypothesis testing using t test (Partial Test). In the study proved that Profitability and Growth Asset partially positive and significant impact on the capital structure while variable size persahaan negative effect on Capital Structure. From this research, the R2 value of 0.683 indicating that the change amounted to 68.3%, which is caused by the independent variable (Profitability, Asset Growth and size of the company) together will affect the capital structure. While the rest of the larger, ie 31.7% explained by other variables that are not entered in the regression model in this study.